Soft budget constraints: An institutional interpretation of stylised facts in economic transformation in Central Eastern Europe - Martin Raiser (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1992)
Among the stylised facts of economic transformation in East Central Europe are the following unpleasant developments-: the reemergence of fiscal deficits, the resilliance of medium inflation, and sluggish output recovery. This paper reviews the major interpretations found in the literature, including structuralist and demand-led approaches, and argues specifically against macroeconomic policy reversal. The concept of soft budget constraints for the state owned enterprise sector is used to develop an institutional interpretation of macroeconomic imbalances in the transformation process. Appropriate indicators of budget softness are derived and applied to the Polish evidence. The results support the hypothesis that current macroeconomic policy concerns are related to the continuing tolerance of loss making firms.The causes of soft budget constraints are found in perverse incentives in the financial sector, unclarified ownership rights, and the political reluctance to face large scale unemployment. A strict enforcement of bankruptcy is urged as a precondition for successful structural transformation.
Keywords: 330; Systemtransformation; Wirtschaftliche Anpassung; Unternehmensfinanzierung; Unternehmensregulierung; Öffentlicher Haushalt; Osteuropa; Polen